(untitled) (Research, Society and Development, 2020)
The school meals is a relevant factor for the children and youth social and educational development, however, the current scenario of the country, states and municipalities is financial contingency. In this sense, this work aimed to map the logistic processes involved in the information flow and materials necessary for the school meals production, and to use the philosophy of constraint theory as an aid in the search for system efficiency. A case study was conducted at the São Gonçalo do Amarante/RN Education Secretary, conducting interviews with those responsible for each process, so as to provide the necessary data to enable the mapping of the processes and the identification of possible problems/bottlenecks, from the perspective of the theory of constraints. After data analysis, it was identified that the municipal school lunch program is divided into three stages, called respectively Planning, Legal Procedures and execution. The execution stage is where the highest rate of problems is concentrated, the most relevant ones are among the receiving, storage and production processes, precisely those that are fully executed in schools, having as main cause the large amount of raw material that it needs to be received and stored at once, which makes the execution processes carried out in schools the restriction of the system.